(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: To evaluate the effect of continuation and discontinuation of oxytocin infusion on maternal and neonatal outcome once the active phase of labour is established. Methods: This is a prospective randomized clinical trial on 100 pregnant women in whom labour was induced on obstetric ground in our institute. Patients were randomly divided in two groups. In the first group oxytocin infusion continued throughout labour and in the second group oxytocin infusion discontinued after establishment of active phase of labour. Result: Consumption of total oxytocin dose, induction-delivery interval, uterine hyperstimulation, caesarean section rate were significantly less in oxytocin discontinued group. Concurrently in oxytocin-continued group rate of postpartum hemorrhage (PPH), neonatal asphyxia, hyperbillirubinemia were higher in comparison to oxytocindiscontinued group. Conclusion: Continuous oxytocin infusion during active phase of labour increases chance of caesarean section, PPH and also of neonatal asphyxia, hyperbillirubenemia. Discontinuation of oxytocin infusion reduces labour risk and gives good neonatal outcome. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.35 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 23-30